1997
DOI: 10.1002/(sici)1097-0142(19970315)79:6<1166::aid-cncr15>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of expression of keratinocyte growth factor and its receptor in endometrial carcinoma

Abstract: factor (FGF) family. KGF is a stromally derived, paracrine growth factor specifically mitogenic for a variety of epithelial cells. The KGF receptor (KGFR), which is a splice ples were obtained at the primary surgery before any treatment was initiated. In addition, endometrial tissues from 19 premenopausal women with normal menstrual cycles were examined. The expression of specific mRNAs in the endometrial samples was assessed using quantitative reverse transcriptase polymerase chain reaction. The results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Our immunohistochemical study also revealed that, in agreement with previous observations in normal epidermal tissues (15,23), KGFR protein appeared distributed over all the epidermal layers, with a preferential localization on the suprabasal spinous layers, in the skin samples analyzed either from normal or psoriatic patients. However, no significant differences in KGFR expression were revealed by quantitative analysis of the immunostaining (data not shown), and several reports demonstrate variability in the expression of KGFR at the protein level in pathological tissues (24,25) including psoriasis (19), as a consequence of the stage of the disease and growth factor stimulation. In fact, it has been suggested that modulation of KGF expression may induce ligand‐dependent KGFR downregulation and consequent modulation in the receptor expression at the protein level (15).…”
Section: Discussionmentioning
confidence: 82%
“…Our immunohistochemical study also revealed that, in agreement with previous observations in normal epidermal tissues (15,23), KGFR protein appeared distributed over all the epidermal layers, with a preferential localization on the suprabasal spinous layers, in the skin samples analyzed either from normal or psoriatic patients. However, no significant differences in KGFR expression were revealed by quantitative analysis of the immunostaining (data not shown), and several reports demonstrate variability in the expression of KGFR at the protein level in pathological tissues (24,25) including psoriasis (19), as a consequence of the stage of the disease and growth factor stimulation. In fact, it has been suggested that modulation of KGF expression may induce ligand‐dependent KGFR downregulation and consequent modulation in the receptor expression at the protein level (15).…”
Section: Discussionmentioning
confidence: 82%
“…Although Pekonen et al (26) failed to show KGF expression in human endometrial adenocarcinoma cells, in our study we detected the presence of KGF transcripts in endometrial cancer cell lines, such as HEC-1 and Ishikawa cells. Siegfried et al (27) suggested that KGF mRNA expression was significantly lower in endometrial adenocarcinoma tissue, compared with cycling endometrial tissue. However, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The KGFR has been detected in human endometrium (10,17), human endometrial carcinoma cells (23), and macaque endometrium (24). Human endometrial KGFR messenger ribonucleic acid (mRNA) is reported to be increased by estrogen (17) and the relative levels of KGFR mRNA in endometrial adenocarcinoma are reported to be similar to those in cycling endometrium (23).…”
mentioning
confidence: 99%